Penatalaksanaan Fisioterapi Pada Pasien Dengan Bell's Palsy Sinistra Di RSUD Sukoharjo - Fadhila, Tiara Hasna; , Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: Bell's Palsy is an accute disorder of peripheral facial nerve, which an emphasis occurs on facial nerve edema, due edema process in the area of the foramen stylomastoideus that the cause is not known or idiophatic. Bell's Palsy cause a problem of physical capacity in which the left facial muscle weakness cause asymetrical face. Purpose: In order to know the physiotherapy management in increasing facial muscle strength and improve muscle functional ability of facial muscle in case Bell's Palsy Sinistra with modalities Electrical Stimulation and Mirror Exercise. Results: After therapy for about six times are obtained the result of improving facial muscle strength with measurement Manual Mucle Testing (MMT) facial muscle on m.Frontalis, m. Corugator Supercilli and m. Bucinator T1: 0 and T6: 1, m. Procerus, m. Orbicularis Oculli, m. Nasalis and m.Mentalis T1: 1 and T6: 3, m. Zigomaticum Mayor, m. Zigomaticum Minor and m. Orbicularis Oris T1: 1 and T6: 1. The increase of functional ability of facial muscle with measurement Ugo Fisch Scale T1: 18 point dan T6: 50 point. This happens because there are some muscle began actively stimulated from the 4th therapy, because the response of some muscle is different. Conclution: Electrical Stimulation and Mirror Exercise can increasing facial muscle strength and increasing in functional ability of facial muscle sinistra. Key words: Bell's Palsy, Electrical Stimulation, Mirror Exercise